Development of Local Wisdom-Based Modules on Pancasila Education Learning of Our Right to Play and Speak for Grade I Primary Students - Septiyani, Vikhy; Hadikusuma Ramadan, Zaka (Jurnal PAJAR (Pendidikan dan Pengajaran), 2025)
The role of a teacher in designing or compiling teaching materials determines the success of the teaching and learning process through teaching materials. Researchers use the Research and Development. The research design is the ADDIE research model. The research data are primary data and secondary data. The techniques used by researchers to collect primary data are interviews, design expert validators, language expert validators, and material expert validators. Secondary data of this research was obtained from books, journals, and theses. The data sources are validators from experts related to validity testing, namely, design, language, and material experts. Based on the research results conducted on the development of local wisdom-based learning modules on the material Our Rights to Play and Speak at SDN 151 Pekanbaru, it can be concluded that the validation results by the three validators for the modules obtained an average percentage of 80% and above with the criteria "Very Eligible". The teacher's response to the module reveals positive results. This is proven by the percentage of questionnaires obtained, 86% and 85.8%, with the criteria "Very Good".